2021
DOI: 10.3390/ijerph18062787
|View full text |Cite
|
Sign up to set email alerts
|

Time–Motion Analysis by Playing Positions of Male Handball Players during the European Championship 2020

Abstract: The aim of this study was to analyze time–motion characteristics of elite male handball players during the last European Championship 2020. A total of 414 players from 24 national teams were analyzed during 65 matches using a local positioning system (LPS) for the first time in a European Championship. Players (n = 1865) covered significantly (p < 0.001; ES = 0.48) more total distance in offense (1217.48 ± 699.33 m) and in all locomotion categories (p < 0.001) than in defense (900.96 ± 538.95 m), with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 26 publications
0
29
0
2
Order By: Relevance
“…Recent studies have validated LPS against well‐known systems such as GPS, showing proper between‐device reliability (coefficient of variation around 5%) 19,20 . A complete description of the system can be found elsewhere 24,25 . The LPS can determine the real‐time position and motion data of the player and ball through lightweight position chips (tags).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have validated LPS against well‐known systems such as GPS, showing proper between‐device reliability (coefficient of variation around 5%) 19,20 . A complete description of the system can be found elsewhere 24,25 . The LPS can determine the real‐time position and motion data of the player and ball through lightweight position chips (tags).…”
Section: Methodsmentioning
confidence: 99%
“…19,20 A complete description of the system can be found elsewhere. 24,25 The LPS can determine the real-time position and motion data of the player and ball through lightweight position chips (tags). The player tag was positioned between shoulder blades using the manufacturer harness, whereas the ball tag was incorporated in the center of the ball.…”
Section: Instrumentationmentioning
confidence: 99%
“…Wings and center backs were more involved in HSR action both in distance (410 ± 193 m and 243 ± 130 respectively) and in number (39.6 ± 18.2 and 34.9 ± 18.1). When time motion was studied [ 5 ], it was shown that wing players spent significantly more time standing and walking than the other players during matches. Technical demands were also playing position-dependent; pivots received and gave up to largely more contacts (58.9 ± 20.3 light contacts and 11.6 ± 3.2 high-intensity contacts [ 6 ] while pivots perform significantly more duels (36.4 ± 16.2) and backs significantly more jumps (19.1 ± 5.2) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These constraints induce that 73% of the ball possession is played in a stabilized attack [ 8 ], as a result, most of the playing time is spent in these phases. Some recent studies have analyzed the difference between the offensive and defensive phase in elite male international players [ 5 , 9 ], however inconsistent results were found for some of the variables (e.g., total distance, walking distance). In both studies, data indicate that players in defense covered a greater distance in high-intensity zones (23% in high-intensity running and 30% in sprinting) than in offense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation